Synthesis, In Vitro Biological Evaluation and In Silico Molecular Docking Studies of Indole Based Thiadiazole Derivatives as Dual Inhibitor of Acetylcholinesterase and Butyrylchloinesterase - Shoaib Khan; Shahid Iqbal; Muhammad Taha; Fazal Rahim; Mazloom Shah; Hayat Ullah; Ali Bahadur; Hamad Alrbyawi; Ayed A. Dera; Mohammed Issa Alahmdi; Rami Adel Pashameah; Eman Alzahrani; et al. (Molecules, 2022)
The current study was conducted to obtain hybrid analogues of indole-based thiadiazole derivatives (1–16) in which a number of reaction steps were involved. To examine their biological activity in the presence of the reference drug Donepezil (0.21 ± 0.12 and 0.30 ± 0.32 M, respectively), the inhibitory potentials of AChE and BuChE were determined for these compounds. Different substituted derivatives showing a varied range of inhibitory profiles, when compared to the reference drug, analogue 8 was shown to have potent activity, with IC50 values for AchE 0.15 ± 0.050 M and BuChE 0.20 ± 0.10, respectively, while other substituted compounds displayed good to moderate potentials. Varied spectroscopic techniques including 1H, 13CNMR and HREI-MS were used to identify the basic skeleton of these compounds. Furthermore, all analogues have a known structure–activity relationship (SAR), and molecular docking investigations have verified the binding interactions of molecule to the active site of enzymes.